1998
DOI: 10.2165/00003088-199835040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Nimesulide

Abstract: Nimesulide is a selective COX-2 inhibitor used in a variety of inflammatory, pain and fever states. After healthy volunteers received oral nimesulide 100 mg in tablet, granule or suspension form the drug was rapidly and extensively absorbed. Mean peak concentrations (Cmax) of 2.86 to 6.50 mg/L were achieved within 1.22 to 2.75 hours of administration. The presence of food did not reduce either the rate or extent of nimesulide absorption. When nimesulide was administered in the suppository form, the Cmax was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
1
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 36 publications
8
68
1
9
Order By: Relevance
“…Several case reports showed that overconsumption of nimesulide or its combination with oral hypoglycaemic drugs was associated with hypoglycaemic episodes in infants and elderly individuals [6,7,9]. Other trials did not document similar interactions between nimesulide and oral hypoglycaemic drugs [6,22,23]. Rofecoxib, one of the new generation of COX2 (PTGS2) inhibitors, was, at the start of this study, one of the biggest selling COX2 (PTGS2) inhibitors of its kind.…”
Section: Introductionmentioning
confidence: 78%
“…Several case reports showed that overconsumption of nimesulide or its combination with oral hypoglycaemic drugs was associated with hypoglycaemic episodes in infants and elderly individuals [6,7,9]. Other trials did not document similar interactions between nimesulide and oral hypoglycaemic drugs [6,22,23]. Rofecoxib, one of the new generation of COX2 (PTGS2) inhibitors, was, at the start of this study, one of the biggest selling COX2 (PTGS2) inhibitors of its kind.…”
Section: Introductionmentioning
confidence: 78%
“…Induction of cytochrome and depletion of glutathione are the major predisposing factors to liver injury (Gupta et al, 2006). The experimental evidence suggests that during metabolism of this type of drug, different reactive metabolites are produced that covalently modify proteins (Bernareggi, 1998), impose oxidative stress (Berson et al, 1991;Ritter & Malejka-Giganti, 1998) and cause mitochondrial injury (Mingatto et al, 2000). Damage to the structural integrity of liver is reflected by an increase in the levels of serum transaminases AST, ALT and ALP, because they are cytoplasmic in location and are released into the circulation after cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…The peak plasma concentration (C max ) is reached 2-3 hours after administration. Plasma concentrations decline mono-exponentially, with an elimination half-life of approximately 4 hours 44 . Studies in patients with osteoarthritis (OA) have shown that relatively high concentrations of nimesulide are rapidly reached in the synovial fluid as well, thus indicating that nimesulide can also modulate inflammatory mediators at the joint level 45 .…”
Section: Consensus Pointmentioning
confidence: 99%